Food Extrusion Technology: Initiatives to Address Food and Nutrition Insecurity in South Africa - Deenanath, Evanie D.; Egal, Abdulkadir (Journal of Pharmacy and Nutrition Sciences, 2017)
The use of extrusion can be regarded as beneficial due to its short production time and wide variety of foods produced by this method. South Africa as a developing country has been involved in food extrusion since the 1980’s and this technology is gaining momentum in academic research areas. A number of research efforts related to extrusion in South Africa have shown the consumption of extruded dry beans can reduce plasminogen activator inhibitor levels in hyperlipidaemic men; the production of sorghum-cowpea extruded instant porridge resulted in a nutritional acceptable product and can be used to supplement the diet of young children to assist with protein deficiencies. Furthermore, research has proven extruder parameters play a role in the outcome of the product and can influence product properties. Based on these research initiatives, Vaal University of Technology/Centre of Sustainable Livelihoods (VUT/CSL) has acquired an Extrusion Pilot Plant to implement interdisciplinary research of nutrition and engineering science. The research will look at process optimisation studies to obtain maximum product output and evaluating nutritional compositions of the products under various conditions. It is hoped the future research efforts at VUT/CSL will address food and nutrition insecurity and showcase the pilot plant as a testing facility and potential advancement to commercialisation.